Social Media as Assistive Technology for Elderly - Sarwat Iqbal,; Kamran Ahsan,; Muhammad Azhar Hussain ,; Adnan Nadeem, (Journal of Basic & Applied Sciences, 2016)
An enormous amount of data is being pooled through the use of social media which is being mined to get benefits in different areas such as healthcare, business, and learning. Providing care to elderly at their home environment is understood as a complex problem and different types of systems are being proposed which can eliminate the presence of caregiver. Social media is acting as the superlative tool to provide elderly a mean of entertainment, communication and information exchange. The data contributed by them can be served to them after converting it into the knowledge. Healthcare professional are interested in the data of elderly so that they can propose solutions to assist them. The organization colleting health data needs the data of elderly activities so they can correlate with other types of activities for their betterment. This work aims to use social media as an assistive technology for elderly which can help them to spend a better life. Different views such as caregiver, healthcare professionals, organization, etc. collecting health data can be benefited through this work. Modern technology such as mobile technology, database, data mining techniques, cloud servers, and user interfaces aiding to make this work possible.